Saving creation: nature and faith in the life of Holmes Rolston III - Preston, Christopher J. (Trinity Univ. Press, 2009)
Known as the "father of environmental ethics," Rolston is celebrated for his advocacy to protect the Earth's biodiversity and for his critical work reconciling evolutionary biology and Christianity. --from publisher description